The relationship between blood pressure and anthropometric measurements of junior high school students in the Municipality of Yogyakarta - Wasilah Rochmah, Wasilah Rochmah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1984)
The relationship between blood pressure and body weight, body height, and other anthropometric measurements, i, e,, upper arm circumference and fat thickness, was studied in 280 junior high school students, aged 12-17 years. Blood pressure was measured by using mercury sphygmomanometer; measurements were conducted once in the sitting position, and the subjects were considered to be normal based on the physical diagnostic examination. The results found showed that there are correlations between either systolic or diastolic blood pressure with anthropometric measÃ¢â¬Â¢ ;urements. Since upper arm circumference indicates the muscle, bone and fat components of the body mass, further study is needed to determine which component has the highest correlation with blood pressure.Key Words: blood pressure - adolescence - anthropometry - nutrition - body mass